If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3x + 4) + -4r = -2(4r + -3) + 2 Reorder the terms: -1(4 + 3x) + -4r = -2(4r + -3) + 2 (4 * -1 + 3x * -1) + -4r = -2(4r + -3) + 2 (-4 + -3x) + -4r = -2(4r + -3) + 2 Reorder the terms: -4 + -4r + -3x = -2(4r + -3) + 2 Reorder the terms: -4 + -4r + -3x = -2(-3 + 4r) + 2 -4 + -4r + -3x = (-3 * -2 + 4r * -2) + 2 -4 + -4r + -3x = (6 + -8r) + 2 Reorder the terms: -4 + -4r + -3x = 6 + 2 + -8r Combine like terms: 6 + 2 = 8 -4 + -4r + -3x = 8 + -8r Solving -4 + -4r + -3x = 8 + -8r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '8r' to each side of the equation. -4 + -4r + 8r + -3x = 8 + -8r + 8r Combine like terms: -4r + 8r = 4r -4 + 4r + -3x = 8 + -8r + 8r Combine like terms: -8r + 8r = 0 -4 + 4r + -3x = 8 + 0 -4 + 4r + -3x = 8 Add '4' to each side of the equation. -4 + 4r + 4 + -3x = 8 + 4 Reorder the terms: -4 + 4 + 4r + -3x = 8 + 4 Combine like terms: -4 + 4 = 0 0 + 4r + -3x = 8 + 4 4r + -3x = 8 + 4 Combine like terms: 8 + 4 = 12 4r + -3x = 12 Add '3x' to each side of the equation. 4r + -3x + 3x = 12 + 3x Combine like terms: -3x + 3x = 0 4r + 0 = 12 + 3x 4r = 12 + 3x Divide each side by '4'. r = 3 + 0.75x Simplifying r = 3 + 0.75x
| 2x+5=6x-9 | | x+-2x+4=3 | | 16+5a=56 | | x^2+4x+4y^2=0 | | 6x+14=5x+12 | | 3(m^2+10m+23)=0 | | r^2+3r=10 | | 7a-7+6a=10-4a | | 3x^2+11x-1-x^3=0 | | y=-2(x+3)2+2 | | x/2=20/10 | | 10t+3(1-4t)= | | x-59=-24 | | A=3.14r*2(5) | | 8m=-14-30 | | x^(2/3)e^x | | 6.5x=7.8 | | 16-4=3x+8-6 | | 4x+4+2x+1= | | .2x+104.8=102 | | 7t+3(1-5t)= | | 4x^2-36x=-85 | | 6+6+3-(-2)= | | 2x+16=X-2 | | n/9.1=7.2 | | 810*(26/45) | | (-3)+3+3= | | 3.50+0.75x=17.00 | | n/9.1=12 | | 3x+5x=7x-8 | | (-88)+x=8 | | 92+x+78=90 |